Opportunities for digital agro-climatic services in the cocoa sector - Giraldo, Diana; Zapata Caldas, Emmanuel; Llanos, Lizeth; Rahn, Eric (2023)
The Alliance Bioversity-CIAT and the Rainforest Alliance (RA) collaborating to explore the value of seasonal climate forecasts for decision-making in cocoa farming. The Alliance Bioversity International-CIAT has extensive experience in using seasonal climate forecasts to improve the management of annual crops (e.g., variety selection, planting time, etc.), but there is limited experience with perennial cropping systems such as cocoa. To this end, we aim to understand which management decisions can benefit from seasonal climate forecasts, which climate variables would require good forecasting skills, and how forecasts need to be translated and communicated to end- users. To achieve this goal, the Alliance Bioversity-CIAT is applying human-centered design (HCD), a creative and participatory approach to problem-solving that allows for a deep understanding of the people for whom we design and the environments in which they live. Stakeholders are considered co-designers in the process of creating solutions or tools, whether digital or non-digital.